Respon Akar Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) di Pre Nursery Pada Pemberian Air dan Pupuk Urea - Yetti Elidar (Agrifarm : Jurnal Ilmu Pertanian, 2016)
The research objective was to determine the effect of water and the volume of urea fertilizer and the interaction of both the oil palm plant roots in the nursery early (pre nursery). This research was conducted in the Nursery Faculty of Agriculture, University of Mulawarman, Samarinda from February to May 2014. The study using completely randomized design (CRD) factorial 3 x 4 with three replications. The first factor is the volume of water (A) in the planting medium consists of three levels, namely: a1 = 100 cc of water plants-1; a2 = 200 cc of water plants-1; a3 = 300 cc water plant-1. The second factor is the provision of urea fertilizer (P), which consists of four levels, namely: p0 = without fertilizer urea; p1 = urea 1 g L-1 water to 100 seedlings; p2 = urea 2 g L-1 water to 100 seedlings; PP3 = urea 3 g L-1 water to 100 seedlings. Number of treatment were 12 and each treatment was repeated three times and each replication consisted of three plants so the total number is 108 plants. Data were statistically analyzed and tested further by testing the smallest Significant Difference (LSD) at 5% level. The results showed that the water volume of 200 cc of plant-1 (p2) provides the highest root dry weight average of 254.13 g. While the interaction between the water volume of 200 cc of plant-1 and dose of urea 3 g L-1 water (a2p3) provides the highest root dry weight average of 300,00 g.